Cybercrime's Threat to Financial Institutions During COVID-19 - Abthal Abdajabar,; Tarik Idbeaa, (AlQalam Journal of Medical and Applied Sciences, 2024)
This systematic review investigates the impact of the COVID-19 pandemic on cybersecurity by examining the rise of cyberattacks targeting financial institutions. By analyzing over 60 sources including academic research, government reports, and security company data, the review reveals a nearly two-fold increase in cybercrimes targeting financial institutions during the pandemic compared to pre-pandemic levels. Phishing attacks are identified as the most prevalent form of cybercrime within this context. The review delves further by analyzing the differences between phishing and other cyberattacks during COVID-19. Based on the results and observations presented in this paper, the analysis will contribute to enriching strategies to address the growing threat of cybercrime in the financial sector. تبحث هذه المراجعة المنهجية في تأثير جائحة كوفيد-19 على الأمن السيبراني من خلال دراسة صعود الهجمات السيبرانية التي تستهدف المؤسسات المالية. ومن خلال تحليل أكثر من 60 مصدرًا بما في ذلك الأبحاث الأكاديمية والتقارير الحكومية وبيانات شركات الأمن، تكشف المراجعة عن زيادة تقارب الضعف في الجرائم الإلكترونية التي تستهدف المؤسسات المالية أثناء الوباء مقارنة بمستويات ما قبل الوباء. وتُعتبر هجمات التصيد الاحتيالي أكثر أشكال الجرائم الإلكترونية انتشارًا في هذا السياق. تتعمق المراجعة بشكل أكبر من خلال تحليل الاختلافات بين التصيد الاحتيالي والهجمات الإلكترونية الأخرى أثناء تفشي فيروس كورونا (COVID-19). وبناء على النتائج والملاحظات المقدمة في هذه الورقة، فإن التحليل سيسهم في إثراء استراتيجيات التصدي للتهديد المتزايد للجرائم الإلكترونية في القطاع المالي